2010
DOI: 10.1002/ptr.3120
|View full text |Cite
|
Sign up to set email alerts
|

Memory performance, brain excitatory amino acid and acetylcholinesterase activity of chronically aluminum exposed mice in response to soy isoflavones treatment

Abstract: Memory performance, brain excitatory amino acid and acetylcholinesterase activity of chronically aluminum (Al) exposed mice in response to soy isoflavones (SI) treatment was investigated in the study. Forty eight mice were allotted randomly into a control group, an Al exposed group (100 mg/kg Al) and an Al exposed group treated with SI (100 mg/kg Al + 60 mg/kg SI) for 60 days. Chronic Al exposure significantly impaired long memory performance in mice as assessed using a passive avoidance task test (χ(2) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…However, SI administration robustly restored elevated MDA levels and decrease of GSH content in SCOP-treated mice, showing a beneficial role in the reduction of oxidative stress. It was similar to the previous founding that effect of SI on learning and memory ability of chronically Al=exposed animals might be related to their anti-oxidative function [ 10 ]. Besides, it has been demonstrated that SI has antioxidant properties via detoxifying free radical species and upregulating antioxidant genes [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, SI administration robustly restored elevated MDA levels and decrease of GSH content in SCOP-treated mice, showing a beneficial role in the reduction of oxidative stress. It was similar to the previous founding that effect of SI on learning and memory ability of chronically Al=exposed animals might be related to their anti-oxidative function [ 10 ]. Besides, it has been demonstrated that SI has antioxidant properties via detoxifying free radical species and upregulating antioxidant genes [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, in the recent years, interest in soybean as a neuroprotective nutrient in the management of AD has increased [ 9 ]. The soy isoflavones (SI), which can be considerd soybean phytochemicals, are thought to be the biologically active components that possess this beneficial effect against neurodegenerative diseases [ 10 ]. Clinical studies have shown that SI improved the cognitive function of postmenopausal women and had beneficial effects on cognition in older adults, especially older adults with AD [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kaizer et al (2008) found increased hypothalamus and striatum AChE and reduced cerebellar, hippocampus and cortex AChE after chronic Al exposures in mice, but reported reduced hypothalamus AChE activity in the Kaizer et al (2005) publication. Reduced rat brain AChE activity was also reported by Bhadauria (2012), Chakrabarty et al (2012), Shrivastava (2012), Stevanović et al (2011), and Thirunavukkarasu et al (2012); however, Ahmed et al (2011), Bihaqi et al (2009), Kakkar and Kaur (2011), Kumar et al (2011), Liu et al (2010), and Sharma et al (2009) all reported increased brain AChE activity, but Xiao et al (2011) found no significant effect of prolonged oral AlCl 3 on mouse brain AChE. Since there are no signs of cholinergic stimulation or inhibition seen after high acute doses of any Al form, the clinical significance of changes in AChE activity (if any) are not clear.…”
Section: Organ Systems and Functionmentioning
confidence: 69%
“…Liu et al (2010) evaluated memory, cerebral cortex, and hippocampus excitatory amino acids (glutamate and aspartate) and brain acetylcholinesterase (AChE) activity in male Kunming mice. Intraperitoneal AlCl 3 was given at 100 mg/kg once every other day for 60 days.…”
Section: Organ Systems and Functionmentioning
confidence: 99%
“…Due to its ability to block Aβmediated formation of calcium permeable ion channel, aluminum can inhibit the increase in calcium levels induced by neurotrophic factors such as BDNF [316][317][318] . The level of other neurotransmitters, such as serotonin, dopamine, glutamate and aspartate, have also been reported to decrease upon aluminum exposure [319,320] . A lower availability of glutamate induced by aluminum has been attributed to the induction of glutamine synthetase and inhibition of glutaminase activity in astrocytes [292] .…”
Section: Aluminum (Al)mentioning
confidence: 99%